2009
DOI: 10.1142/s0219876209001784
|View full text |Cite
|
Sign up to set email alerts
|

On the Convergence of the Kriging-Based Finite Element Method

Abstract: An enhancement of the FEM using Kriging interpolation (K-FEM) was recently proposed. This method offers advantages over the conventional FEM and mesh-free methods. With Kriging interpolation, the approximated field over an element is influenced not only by its own element nodes but also by a set of satellite nodes outside the element. This results in incompatibility along interelement boundaries. Consequently, the convergence of the solutions is questionable. In this paper, the convergence is investigated thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…This means the elemental piecewise KI is not fully compatible across the interelement boundaries. Its effect on the convergence was studied in the context of 2D elastostatic problems [14,15]. It was found that K-FEM with appropriate choice of correlation function passes the weak patch test and therefore the convergence can be guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…This means the elemental piecewise KI is not fully compatible across the interelement boundaries. Its effect on the convergence was studied in the context of 2D elastostatic problems [14,15]. It was found that K-FEM with appropriate choice of correlation function passes the weak patch test and therefore the convergence can be guaranteed.…”
Section: Discussionmentioning
confidence: 99%
“…6, a polynomial basis function and a correlation function should be chosen. Basis functions ranging from polynomial of the degree one up to four have been utilized in the past works on the K-FEM [2][3][4][5][6][7][8][9][10][11].…”
Section: Kriging Interpolation In the K-femmentioning
confidence: 99%
“…Following the previous works [3][4][5][6][7][8][9][10], Gaussian and Quartic Spline correlation function (QS) were chosen. Gaussian correlation function is defined as…”
Section: Kriging Interpolation In the K-femmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the Kriging-based elements are nonconforming. The issue of non-conformity and its effects on the convergence characteristics has been addressed in Reference [4]. It was found that despite the non-conformity, solutions of the K-FEM with a quartic spline correlation function and appropriate Kriging parameters always converge to the exact solutions.…”
Section: Introductionmentioning
confidence: 99%